Children's Opinions about the Loss of Nature - Abraham A. Mabelis Alterra (Environmental Association of Southern Africa, 2005)
A survey was conducted among approximately 400 Dutch schoolchildren (age: 8-16 years) in order to test their feelings about deterioration of the environment and the extinction of species. The majority of pupils answered that they regret the extinction of species more or less, especially popular ones. For a minority it does not matter at all. The proportion of pupils who expressed indifference to the pollution of air, water and soil was 7%, 10% and 13%, respectively. Dying of the forest was taken very seriously by approximately 60% of the pupils; this percen tage increased after a slide of a dead forest was shown. A similar result was obtained in respect to the assumed extinction of a common plant species: it was taken more seriously after some information was given. More than half of the pupils predicted a bad future for the Netherlands. However, this pessimistic view can be changed into a more optimistic one by stimulating activities to improve the environment. The fact that most pupils judged their own future positive may indicate that they feel to have some control on the quality of their own life.